FACTORS ASSOCIATED WITH DELAYED UPTAKE OF GLASSES AMONG PATIENTS WITH REFRACTIVE ERRORS AT JINJA REGIONAL REFERRAL HOSPITAL. A CROSS-SECTIONAL STUDY. - Asiimwe, Anicent; Kyakulaga, Adonia (Student’s Journal of Health Research Africa, 2025)
Background. Despite the known benefits of wearing glasses for correcting refractive errors, there is a significant delay in the uptake of glasses among patients at Jinja Referral Hospital. This study determined factors associated with delayed uptake of glasses among patients with refractive errors at Jinja Regional Referral Hospital. Methods. It was a cross-sectional descriptive study, using quantitative methods was conducted among patients attending Jinja regional referral hospital eye clinic. 100 Respondents were selected by non-probability convenient sampling. Data was analyzed using Excel data base to for quantitative data which was presents in tables and graphs. Results. 46(46%) of the participants were males, 12(27.78%) were in the age range of 41-50 years, and 41.67% of those participants were diagnosed with visual impairment. 65% of the respondents reported concerns about the social stigma of wearing glasses. The stigma was more pronounced among men (70%), 50% of both men and women felt that wearing glasses affected their appearance particularly younger individuals, 70(70%) of the participants were not aware that glasses can improve vision, 57(57%) were not aware of potential consequences of not correcting refractive errors timely and 52(52%) had not received information about timely correction of refractive errors from health care providers. Conclusion. The study established that several key factors, including demographic characteristics, low awareness levels, and social attitudes, significantly contribute to the delay in adopting corrective eyewear. Younger individuals and males were more likely to delay, while limited awareness and social stigma surrounding glasses further exacerbated the issue. Recommendations. To improve awareness of the importance of vision correction, the Ministry of Health, in collaboration with Jinja Regional Referral Hospital and community leaders, should launch targeted awareness campaigns within the next six months.